The Influence of Resilience on Job Performance: The Mediating Role of Work Engagement Among Banking Employees in Jakarta - Endah Wulan Safitri, (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
The purpose of this study is to explore whether job performance can be influenced by the resilience obtained by employees and whether work engagement can serve as a mediator in this influence. Using a quantitative approach, the researcher involved 103 samples consisting of employees from various banks in Jakarta and different divisions within those banks. The collected data were primary, based on survey questionnaires distributed randomly and analyzed using SEM-PLS techniques assisted by the SmartPLS software. The findings indicate that resilience significantly positively affects employee performance (p-value: 0.000; t-statistic: 5.215) and in this study, it was proven that work engagement acts as a mediating variable (p-value: 0.030).